2023
DOI: 10.31219/osf.io/zjg5e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Practice in study abroad contexts

Abstract: This chapter reviews current findings about practice during study abroad from a Skill Acquisition Theory perspective. The chapter begins by reviewing main findings from the study abroad literature about linguistic development and then considers how researching learners’ social networks can contribute to theorization about practice in L2 development. Also reviewed are how three principles of effective practice can help us to understand the specific ways that practice can lead to L2 development as well as how SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…As expected, the stay‐abroad experience was associated with a better performance on the comprehension test but did not seem to correlate with the presence of context. This substantially adds to empirical evidence from previous studies, which found stay‐abroad experience to be a powerful predictor of L2 metaphor comprehension (Suñer, 2018; De Cock & Suñer, 2018), and more generally to research into lexis development in study abroad language learning contexts (McManus, 2023). Stay‐abroad experiences are considered to provide learners with valuable opportunities for communication practice in a wide range of formal and informal settings and thus increased exposure to registers that are rarely covered in textbooks, as is the case for linguistic taboo (Berdún Villamonte, 2021).…”
Section: Discussionsupporting
confidence: 63%
“…As expected, the stay‐abroad experience was associated with a better performance on the comprehension test but did not seem to correlate with the presence of context. This substantially adds to empirical evidence from previous studies, which found stay‐abroad experience to be a powerful predictor of L2 metaphor comprehension (Suñer, 2018; De Cock & Suñer, 2018), and more generally to research into lexis development in study abroad language learning contexts (McManus, 2023). Stay‐abroad experiences are considered to provide learners with valuable opportunities for communication practice in a wide range of formal and informal settings and thus increased exposure to registers that are rarely covered in textbooks, as is the case for linguistic taboo (Berdún Villamonte, 2021).…”
Section: Discussionsupporting
confidence: 63%